Technical Overview Of Biogas Utilization as Fuel of Boat Engine - Nilam Sari Octaviani; Semin Semin (Institut Teknologi Sepuluh Nopember, 2018)
The depletion of world energy reserves and the increasing levels of environmental pollution, increase human creativity. Discoveries on environmentally friendly renewable energy-making technologies are increasingly widespread. One of them is the manufacture and utilization of biogas as an alternative fuel. Biogas is one of renewable energy sources with bio gas production process from organic material like cattle dung with the help of bacteria decomposers. By conducting a literature study on biogas utilization and calculation analysis, biogas application was applied as an outboard fuel engine with 10 horse power in a boat capable of crossing for 10 minutes with a capacity of 1 to 2 passengers, such as private boats owned by coastal communities or boats used by traders on floating markets in the Kalimantan area.